First record of the bougainvillea mealybug Phenacoccus peruvianus in Greece - Gkounti, Vasiliki; Milonas, Panagiotis (ENTOMOLOGIA HELLENICA, 2013)
This is the first record of the Boungainvillea mealybug Phenacoccus peruvianus in Greece. The mealybug originates from South America and in the last decade has invaded Europe and particularly the Mediterranean basin. It has become a major pest for various ornamental plant species. In Spain, it is found to be parasitized by the parasitoid Acerophagus n. sp. near coccois.